Effects of Blood Transfusion on the Risk of Hepatitis C Infection in Hemodialysis Patients: A Meta-Analysis - Astuti, Yuli; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: It is estimated that 2% of the world's population (about 123 million people) was infected with hepatitis C. Blood transfusion is one of the therapies, but this therapy is at risk of being a transmission me